2011
DOI: 10.1094/phyto-10-10-0270
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pathogenic Relatedness of Pseudoperonospora cubensis and P. humuli

Abstract: The most economically important plant pathogens in the genus Pseudoperonospora (family Peronosporaceae) are Pseudoperonospora cubensis and P. humuli, causal agents of downy mildew on cucurbits and hop, respectively. Recently, P. humuli was reduced to a taxonomic synonym of P. cubensis based on internal transcribed spacer (ITS) sequence data and morphological characteristics. Nomenclature has many practical implications for pathogen identification and regulatory considerations; therefore, further clarification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 46 publications
4
44
0
Order By: Relevance
“…Given that physiological specialization in P. cubensis is manifested among species and genera within the Cucurbitaceae, an intriguing but unexplored area is whether physiological specialization similarly occurs in P. humuli beyond Humulus lupulus. If confirmed, this could in part explain conflicting reports of P. humuli infection of cucurbit species (63,91).…”
Section: Pathogenic Variationmentioning
confidence: 96%
See 3 more Smart Citations
“…Given that physiological specialization in P. cubensis is manifested among species and genera within the Cucurbitaceae, an intriguing but unexplored area is whether physiological specialization similarly occurs in P. humuli beyond Humulus lupulus. If confirmed, this could in part explain conflicting reports of P. humuli infection of cucurbit species (63,91).…”
Section: Pathogenic Variationmentioning
confidence: 96%
“…Although these studies suggest that P. cubensis can potentially infect hop, low levels of compatibility in cross-inoculations suggest that each species is best adapted to its primary host. Further, evidence based on genetic markers does not indicate occurrence of either species on the other host (63). Inference of gene flow between the two species will require a large number of loci and more powerful tools for genetic analysis (38).…”
Section: Lineages and Mating Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, results from studies using more genetic markers support the species distinction between P. humuli and P. cubensis with nrITS, coxII , and ypt1 (Runge, Choi & Thines, 2011) . Furthermore, the idea of two distinct species was supported through phylogenetic analysis of nrITS, B-tub , and cox2 (Mitchell et al, 2011). However, it was found that in laboratory settings, P. cubensis can infect hop and have light sporulation and that P. humuli can infect cucumber with limited success (Mitchell et al, 2011; Runge & Thines, 2012).…”
Section: Introductionmentioning
confidence: 99%